A Possible Interpretation for the High Catalytic Activity of Heat-Treated Non-Precious Metal Nx/C Catalysts for O 2 Reduction in Terms of Their Formal Potentials - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Ponce-Hormazabal, I; Venegas-Toledo, R (2012)
Sin Editorial Disponible